Synthesis of tin octoate coating on ceramic support derived from ceramic waste in production of polylactic acid / Amira Nadzirah Suhaidi - Suhaidi, Amira Nadzirah (2021)
Production of polylactic acid (PLA) using liquid tin octotate (homogeneous catalyst) can lead to degradation of PLA after certain time. The aim of this study is to fabricate heterogeneous tin octoate on ceramic support from ceramic waste in the production of polylactic acid. The research began with the collection of ceramic waste collected from sanitary ware company and ceramic support were produced. Next, the support then were coated with tin octoate mixture formulation with variation on sintering temperature, binder, solvent and catalyst concentration. The samples of coating on ceramic support were sent for characterization using EDX and adhesion testing of tape test ASTM D3359. With this analysis, the optimum conditions for the surface coating were formulated using tin octoate of 500ppm, polyethylene glycol (PEG) binder and N,N-dimethylformamide (DMF) solvent and sintered at 200 ℃. Subsequently, the ring opening polymerization of lactide were undergone with different phase of catalyst, initiators and temperature of reaction. The samples of polymerization reaction product were sent for characterization using Fourier Transform Infrared (FTIR) in finding the functional group in the product and UV-Vis Spectrophotometer at absorbance of 232 nm in finding the existence and concentration of the product. The reaction with heterogeneous catalyst achieved highest polymerization rate of 92.4 ppm at 130 ℃ of reaction temperature. Excellence result showed using methanol initiator at polymerization rate of 70.8 ppm of product. This study has proven that the heterogeneous tin octoate with reaction temperature of 130 ℃ and using methanol initiator can be used in the production of polylactic acid.